Pengaruh Perusahaan Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Bayu Wulandari; Mettania Kirana; Helnia Oktavia Sitanggang; Jayana Jayana (COSTING : Journal of Economic, Business and Accounting, 2021)
This research was aimed to evaluate whether there is a Leverage, Total Assets Turnover, Earning per Share, Current Ratio, Profitability, and Firm Size have related to dividend policy of manufacturing companies which is registered on Indonesia stock exchange in period 2017-2019. This research is included in type of quantitative descriptive research which uses data from 162 manufacturing companies that is registered on Indonesia stock exchange in period 2017-2019. This research also uses purposive sampling method that have 52 samples. Data in this research are all of the financial reports from each company that is published on www.idx.co.id. The variables related in this research are leverage, tato, eps, current ratio, profitability, and firm size. The research’s method uses descriptive analysis and multiplelinear regression analysis. The result of this study shows that Leverage have a negative effect to dividend policy, Total Assets Turnover have a negative effect to dividend policy, Earning per Share does not have a negative and significant to dividend policy, Current Ratio have a negative effect to dividend policy, Profitability does not make a significant contribution to dividend policy, and Firm Size does not have a negative and significant to dividend policy of manufacturing companies on Indonesia stock exchange. Simultaneously, Leverage, Total Assets Turnover, Earning per Share, Current Ratio, Profitability, and Firm Size together have a significant with dividend policy of manufacturing companies on Indonesia stock exchange. Keywords : Leverage, Total Assets Turnover, Earning per Share, Current Ratio, Profitability, Firm Size, and Dividend Policy.